Fracture of concrete containing crumb rubber - Grinys, Audrius; Sivilevičius, Henrikas; Pupeikis, Darius; Ivanauskas, Ernestas (Journal of Civil Engineering and Management, 2013)
Every year, colossal amounts of used and non-biodegradable rubber tyres are accumulated in the world. Experience shows that the most efficient way to increase the concrete fracture energy G F (N/m) is to use metal or polypropylene fibres. The optimal content of fibre increases concrete resistance to stress (especially tensile stress under bending force). Concrete fracture is not brittle; concrete continues deforming after maximum stresses and is able to resist certain stresses, there is no abrupt decrease in loading. The research has proved that crumb rubber can be used in concretes as an alternative to metal and polypropylene fibres. The investigation has found that rubber waste additives, through their specific properties can partly take up tensile stresses in concrete and make the concrete fracture more plastic; besides, such concrete requires a significantly higher fracture energy and concrete samples can withstand much higher residual strength at 500 µm crack mouth opening displacement (CMOD) and deflection.